Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif pada Mata Pelajaran Sains Materi Tata Surya Menggunakan Model APPED (Studi Kasus: SD Brawijaya Smart School) - Ghasa Faraasyatul 'Alam; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The integrated educational institution of SD Brawijaya Smart School applies various innovations and creations on information technology that are used to grow and develop the potential in students. However, in Science subjects Solar System material for class VI media used is still standard with the use of textbooks and illustrated paper. Support solutions implemented by developing interactive multimedia-based learning media using the APPED model. The stages of R & D (Research and Development) type research from the APPED model are to carry out initial analysis and research, design, production, evaluation and dissemination. All components in the test results of the ongoing evaluation have worked well according to three specific criteria and the developer has proven all valid results. While the results of the validation of income, the percentage of alpha testing was 95.5% by material experts, 92.5% by instructional experts, and 88.8% by media experts. Therefore, according to the experts it was declared valid and according to the criteria of